Impact of Non-steroidal Anti-inflammatory Drug Administration for 12 Months on Renal Function - Hayashi, Kazuhiro; Miki, Kenji; Kajiyama, Hiroshi; Ikemoto, Tatsunori; Yukioka, Masao (Frontiers in Pain Research, 2021)
Background: The use of non-steroidal anti-inflammatory drugs (NSAIDs) is associated with an increased risk of renal complications. Resolution of renal adverse effects after NSAID administration has been observed after short-term use. Thus, the present study aimed to investigate a series of patients with chronic musculoskeletal pain who underwent long-term NSAID administration followed by switching to tramadol hydrochloride/acetaminophen (TA) combination tablets to study the impact of NSAID-induced renal adverse effects. Methods: This was a longitudinal retrospective study of 99 patients with chronic musculoskeletal pain. The patients were administrated with NSAIDs daily during the first 12 months, followed by daily TA combination tablets for 12 months. Estimated glomerular filtration rate (eGFR) and serum levels of aspartate aminotransferase and alanine transaminase were measured at baseline, after NSAID administration and after TA administration. Results: eGFR was significantly reduced after 12-month NSAID administration (median, from 84.0 to 72.8 ml/min/1.73 m2), and the reduction was not shown after the subsequent 12-month TA administration (median, 71.5 ml/min/1.73 m2). Reduction in eGFR was less in patients who received celecoxib (median, −1.8 ml/min/1.73 m2) during the first 12 months. There was no significant difference in aspartate aminotransferase and alanine transaminase in each period. Conclusions: Thus, patients receiving NSAIDs for 12 months displayed both reversible and irreversible reduction of eGFR upon cessation of NSAIDs and switching to TA. Our data highlight the potential safety benefit of utilizing multimodal analgesic therapies to minimize the chronic administration of NSAIDs.